Parallel interrogation of covalent intermediates in the biosynthesis of gramicidin S using high-resolution mass spectrometry - Miller, Leah M. (Cold Spring Harbor Laboratory Press, 2005)
For determination of multiple covalent intermediates bound to the ultra-large enzymes responsible for biosynthesis via nonribosomal peptide synthesis, mass spectrometry (MS) is a promising method to provide new mechanistic insight. Application of a quadrupole-Fourier-transform instrument (Q-FTMS) for direct analysis of aminoacyl intermediates is demonstrated for the first two modules (127 and 120 kDa) involved in the nonribosomal synthesis of gramicidin S. Cyanogen bromide digestions of recombinant proteins afforded detection of two active site peptides (both ~13 kDa) that provided direct evidence for modules copurifying with their preferred amino acid substrates. Given the ability to detect multiple covalent intermediates in tandem, a competition experiment among several nonnatural substrates in parallel was performed using the first module. This defined mixture of acyl-enzyme intermediates was used to probe the selectivity of the condensation step producing a diversity of noncognate dipeptides on the second module.